2009
DOI: 10.1111/j.1708-8208.2009.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Changes in the Peri-Implant Soft Tissues Assessed by Directional Cutaneous Kinaesthesia and Graphaesthesia: A Prospective Study

Abstract: The DCK and G are simple but reliable sensory tests that can be easily applied in the oral region. This prospective study indicates that tooth loss reduces tactile function compared with implant-supported prostheses. The peri-implant soft tissues could be partially involved in the osseoperception function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…72,76 Both of these tests correlate the physiologic function of the receptors to the subjective response of the patient. 77 A study by Macefield et al confirmed that the tactile response decreased at the level of abutment connection, after stage-two surgery. This can be due to the trauma caused by two surgical procedures (flap surgery for implant placement and implant uncovering surgery) involving periosteal elevation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…72,76 Both of these tests correlate the physiologic function of the receptors to the subjective response of the patient. 77 A study by Macefield et al confirmed that the tactile response decreased at the level of abutment connection, after stage-two surgery. This can be due to the trauma caused by two surgical procedures (flap surgery for implant placement and implant uncovering surgery) involving periosteal elevation.…”
Section: Discussionmentioning
confidence: 94%
“…Graphaesthesia is the perception of figures drawn on the skin . Both of these tests correlate the physiologic function of the receptors to the subjective response of the patient …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The threshold level of ATS was recorded and ranged between 20 and 150 µm depending on the dental status, with a 2-5 times increased threshold for implants compared to natural teeth. [29][30][31][32][33][34][35] In another six articles, 2,[36][37][38][39][40] pressure was manually or semi-automatically exerted on natural teeth and implant-supported prostheses, and the threshold of passive tactile sensibility (PTS) revealed an up to 50 times higher threshold level for implants (force = 100 g) compared to natural teeth (force = 2 g). Overall, implant-supported prosthesis showed higher tactile force threshold level compared to natural teeth but remained more sensitive than the non-implant-supported prosthesis.…”
Section: Histological Evidencementioning
confidence: 99%